FINANCIAL DISTRESS AND ITS EFFECT ON STOCK RETURN OF CONSTRUCTION AND BUILDING COMPANIES BEFORE AND DURING PANDEMIC COVID-19 - Aini Nurachman Dini; Hermanto Siregar; Moch. Hadi Santoso (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to analyze financial distress conditions and stock returns of the construction and building sub-sector companies before and during COVID-19 pandemic, analyze the factors that affect financial distress conditions, and analyze the effect of financial distress on stock returns. The study was conducted on 14 construction and building sub-sector companies listed on IDX from 2018q1 to 2021q4 using the panel data regression and two stages least square method. During the Covid-19 pandemic, there is a decrease in DSCR average value and an increase in the number of companies classified as distressed. Safe companies had negative average stock returns, while distressed companies had positive average stock returns. Meanwhile, factors that affect financial distress are profitability, liquidity, and rupiah exchange rate. Therefore, the company is expected to increase profitability and maintain optimal liquidity value in order to avoid financial distress condition. To improve the accuracy of investment decision, investors need to pay attention to the fundamental conditions and operational performance of the company. The interaction variable between financial distress proxied by predictive value of DSCR and the growth rate of confirmed cases of COVID-19 has a significant negative effect on stock returns.